Analysis of the effects of time pressure and supervisor support on organizational cynicism and employee surveillance in organization - Adıgüzel, Zafer; Karaalioğlu, Sevgi Nur; Zehir, Cemal (CEIPA Business School, 2021)
Objective. Analyze the relationships between the variables of employee surveillance, supervisor support, organizational cynicism, and time pressure. Methodology. The sample group of the study consists of 417 white-collar employees in private and public sector. After the analysis of the findings were made with the SPSS 25 program, the results were analyzed and evaluated. Analysis data were collected from both public and private institutions operating in Istanbul. Results. As a result of the analysis, it is understood that time pressure and supervisor support have significant effects on organizational cynicism and employee surveillance. Conclusions. With the analysis of the data received in the scope of research model, it may be drawn a conclusion that employees expect support from their supervisors, otherwise they start to move away from the institution.

Objetivo. Analizar las relaciones entre las variables de vigilancia de los empleados, apoyo del supervisor, cinismo organizacional y presión del tiempo. Metodología.El grupo de muestra del estudio está formado por 417 empleados de cuello blanco del sector privado y público. Los resultados se analizaron y evaluaron con el programa SPSS 25. Los datos del análisis se recogieron en instituciones públicas y privadas que operan en Estambul. Resultados. Como resultado del estudio se entiende que la presión del tiempo y el apoyo del supervisor tienen efectos significativos sobre el cinismo organizativo y la vigilancia de los empleados. Conclusiones. Con el análisis de los datos recibidos en el ámbito del modelo de investigación se puede concluir que los empleados esperan el apoyo de sus supervisores, de lo contrario comienzan a alejarse de la institución.

Objetivo. Analise as relações entre as variáveis de vigilância do funcionário, suporte do supervisor, cinismo organizacional e pressão de tempo. Metodologia. O grupo de amostra do estudo é composto por 417 funcionários de colarinho branco dos setores público e privado. Os resultados foram analisados e avaliados com o programa SPSS 25. Os dados para análise foram coletados em instituições públicas e privadas que operam em Istambul. Resultados. Como resultado do estudo, entende-se que a pressão do tempo e o apoio do supervisor têm efeitos significativos no cinismo organizacional e na vigilância dos funcionários. Conclusões. Com a análise dos dados recebidos no âmbito do modelo de pesquisa, pode-se concluir que os funcionários esperam o apoio de seus supervisores, caso contrário, começam a se afastar da instituição.
Análisis de los efectos de la presión del tiempo y el apoyo del supervisor sobre el cinismo organizativo y la vigilancia de los empleados en las organizaciones
Keywords: Employee Surveillance; Supervisor Supportor; Organizational Cynicism; Time Pressure; Hayes Process; Vigilancia de los Empleados; Apoyo del Supervisor; Cinismo Organizacional; Presión del Tiempo; Proceso Hayes; Vigilância do Funcionário; Suporte do Supervisor; Cinismo Organizacional; Pressão do Tempo; Processo Hayes